Antibacterial activity of ethanol extract of limpasu (Baccaurea lanceolata) pericarpium with the ultrasound assisted extraction method against Propionibacterium acne - Ulpah, Rusmili; Nashihah, Siti; Zamzani, Irfan (Pharmacy Department, Faculty of Health Sciences, Jenderal Soedirman University, Purwokerto, Indonesia, 2023)
Background: Acne, a prevalent skin condition, can arise from factors such as an unhealthy lifestyle, dietary habits, hormonal imbalances, and bacterial infections. Propionibacterium acnes is a notable bacterium responsible for acne. In South Borneo, the pericarpium of the limpasu plant (Baccaurea lanceolata) is traditionally used to treat acne. Objective: This study aims to scientifically validate the empirical antibacterial effects of limpasu pericarpium against Propionibacterium acnes, as reported by the communities in South Borneo. Methods: The ultrasound-assisted extraction (UAE) method was utilized to extract compounds from limpasu pericarpium. The antibacterial activity of the limpasu pericarpium extract was evaluated using the disc diffusion method at concentrations of 20%, 40%, 60%, 80%, and 100% w/v. Clindamycin served as the positive control, and 1% DMSO was the negative control. Results: The lowest concentration (20%) fell within the strong activity category, producing a clear zone diameter of 18.76 mm. Higher concentrations (40%, 60%, 80%, and 100%) demonstrated more potent antibacterial effects, with inhibition zones of 23.23 mm, 26.06 mm, 26.93 mm, and 27.33 mm, respectively. Notably, 60% to 100% concentrations exhibited greater inhibitory effects than the positive control, clindamycin, which had an inhibition zone of 25.23 mm. Conclusion: The study confirms the antibacterial properties of limpasu pericarpium against Propionibacterium acnes, supporting the traditional claims of its efficacy by the South Borneo communities.